Orbital Metastasis as the Initial Manifestation of Lung Adenocarcinoma: 18F-FDG PET-CT Findings - Salah, Oueriagli Nabih; Meryem, Aboussabr; Omar, Ait Sahel; Abderrahim, Doudouh (World Journal of Nuclear Medicine, 2025)
Orbital metastases from malignant tumors are uncommon. In 25% of cases, they are the first sign of an undiagnosed cancer, and they account for approximately 7 to 12% of lung cancer cases. A lack of awareness about this condition can lead to misdiagnosis, distinguishing malignant from benign lesions. We present the case of a 65-year-old patient with orbital metastasis from lung cancer. 18F-fluorodeoxyglucose (18F-FDG) positron emission tomography/computed tomography (PET/CT) was crucial in diagnosing this, revealing hypermetabolism in the left lung mass as well as intense uptake in the right retro-orbital region, which was confirmed as orbital metastasis through cerebro-orbital magnetic resonance imaging. For 2 months, our patient had right eye pain and decreased visual acuity and no attention was paid to these symptoms. Through this clinical case, the authors highlight the utility of 18F-FDG PET/CT in the diagnosis of primary malignancy in lung cancer patients, who presented with orbital metastasis as the first sign.
Keywords: 18F-FDG; lung adenocarcinoma; orbital metastasis; PET/CT